Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan Peta Pikiran Terhadap Hasil Belajar Tematik Siswa Kelas V SDN 01 Bengkulu Tengah - Aidiyana Auva; Daimun Hambali; Resnani Resnani (JURIDIKDAS, 2021)
This study aims to analyze the influence of Jigsaw type cooperative learning model with a mind maps on Thematic learning outcomes in grade V SDN 01 Bengkulu Tengah. This research is a quantitative research. The research method used was Quasi Experimental with Matching Only Pretes-Posstet Control Group Design. The population of this research is the class V students of SDN 01 Bengkulu Tengah and the sample is the VB class as an experimental class and VA class as a control class taken using the Random Sampling technique. The instrument used for the aspect of knowledge consisted of multiple choice question tests given through Pretest and Posttest, while for the attitude and skills aspects used observation sheets. Data analysis techniques used descriptive analysis, prerequisite test analysis, hypothesis test analysis and observations. From the results of the research found tcount (3.25) > ttable (2.01) in Indonesian subjects and tcount (2.70) > ttable (2.01) in Social Sciences subjects. The tcount obtained higher than the ttable announced that the experimental class using a Jigsaw type cooperative learning model with a mind map than the conventionally implemented control class, while the attitude and skills aspects show significant differences between sample classes. Be concluded, that there was an influence of Jigsaw type cooperative learning model with a mind maps on Thematic learning outcomes in grade V SDN 01 Bengkulu Tengah.